Impact of Educational Intervention on Knowledge Regarding HIV/AIDS among Adults - Sharma, Muna (Journal of Nepal Health Research Council, 2009)
Background: HIV/AIDS is the genuine public health problem; in which prevention is the mainstay of the response where adult can play principle role in the society. The study aimed at finding out the effectiveness of the education intervention in improving knowledge among adults regarding the HIV/AIDS. Methods: A pre- experimental semi structured interview was conducted to measure research variables among a group of 67 adults, who were the members of Local Community Organizations (LCOs) of Bagashori VDC of Bhaktapur in pre- test and post test. The obtained data was analyzed by using descriptive and inferential statistics. Results: The findings revealed that after intervention respondents had significantly higher (p= 0.001) mean knowledge about HIV/AIDS. Conclusion: The test confirmed that the education program on HIV/AIDS was able to considerably improve people’s knowledge about HIV/AIDS. Key words: Adults; Educational intervention; Knowledge; HIV/AIDS doi: 10.3126/jnhrc.v6i2.2213 Journal of Nepal Health Research Council, Vol. 6, No. 2, 2008, October. Page: 102-106